2019
DOI: 10.1002/adsc.201900048
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Stereoselective Synthesis of 3‐Pyrazolylidene‐2‐oxindole Compounds by Nucleophilic Vinylic Substitution of (E)‐3‐(Nitromethylene)indolin‐2‐one

Abstract: Vila, C.; Slack, S.; Blay, G.; Muñoz Roca, MDC.; Pedro, JR. (16-0). Regio-and Stereoselective Synthesis of 3-Pyrazolylidene-2-oxindole Compounds by Nucleophilic Vinylic Substitution of (E)-3-(Nitromethylene)indolin-2-one. Advanced Synthesis & Catalysis. 361(8):Abstract. A highly regio-and stereoselective synthesis of 3-alkylidene-2-oxindoles has been described through a nucleophilic vinylic substitution (SNV) of (E)-3-(nitromethylene)indolin-2-one using pyrazol-3-ones as nucleophiles and Et3N as a base. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…By the action of one quinuclidine moieties of (DHQ) 2 Pyr, the pyrazol‐3‐one 2 is activated by hydrogen bonding, for the regioselective nucleophilic addition of the pyrazol‐3‐one to the α‐position of nitroalkene 1 , that could be coordinated to the catalyst by π–π stacking interactions. After the nucleophilic addition of 2 , the intermediate switches to an eclipsed conformation, which is favored by an intramolecular hydrogen bond between the nitro group and the hydrogen of the C‐3 of oxindole through a five‐membered ring , . In this case, in the presence of a base [the quinuclidine moiety of the (DHQ) 2 Pyr catalyst], the hydrogen bond prompts a fast 1,2‐ cis ‐elimination to afford the E ‐3‐alkenyl‐2‐oxindole 3fa as the major product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By the action of one quinuclidine moieties of (DHQ) 2 Pyr, the pyrazol‐3‐one 2 is activated by hydrogen bonding, for the regioselective nucleophilic addition of the pyrazol‐3‐one to the α‐position of nitroalkene 1 , that could be coordinated to the catalyst by π–π stacking interactions. After the nucleophilic addition of 2 , the intermediate switches to an eclipsed conformation, which is favored by an intramolecular hydrogen bond between the nitro group and the hydrogen of the C‐3 of oxindole through a five‐membered ring , . In this case, in the presence of a base [the quinuclidine moiety of the (DHQ) 2 Pyr catalyst], the hydrogen bond prompts a fast 1,2‐ cis ‐elimination to afford the E ‐3‐alkenyl‐2‐oxindole 3fa as the major product.…”
Section: Resultsmentioning
confidence: 99%
“…After the nucleophilic addition of 2, the intermediate switches to an eclipsed conformation, which is favored by an intramolecular hydrogen bond between the nitro group and the hydrogen of the C-3 of oxindole through a five-membered ring. [13,14] In this case, in the presence of a base [the quinuclidine moiety of the (DHQ) 2 Pyr catalyst], the hydrogen bond prompts a fast 1,2-cis-elimination to afford the E-3-alkenyl-2oxindole 3fa as the major product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have been made for its effective synthesis, and also for the stereoselective synthesis of (E) and (Z) diastereomers. [27][28][29][30][31] Accordingly, the kinetics of the E/Z isomerization of the designed molecules seemed to be of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we envisioned that the cross coupling between the C­( sp 3 ) of 3-substituted oxindoles 2 and the C­( sp 2 ) of nitro olefins 1 could forge the desired bisoxindole derivatives 3 bearing a vinyl-substituted all-carbon quaternary stereocenter, triggered by the elimination of HNO 2 . However, the regioselectivity of this transformation might be difficult to control, as the reactivity at the α - and β -positions of electrophile 1 is the balance of electron property and steric hindrance . Previous studies have demonstrated that both of these positions are reactive toward nucleophilic partners .…”
mentioning
confidence: 99%